Biophilic urbanism : designing resilient communities for the future - Tabb, Phillip (New York, NY : Routledge, 2021)
"Biophilic Urbanism provides readers with the tools to create more nature-based urban environments that are climate positive, sustainable, and healthy. The principles of biophilia are intended to support appreciation and direct engagement with nature, to responsibly utilize on-site natural resources, to plan according to climatic conditions and local ecological processes. It seeks to create resilient and equitable human places capable of providing critical life-support functions and a strong sense of community, and to foster experiences that raise the human spirit creating a sense of awe. Twenty-five pattern attributes are defined and explored, each of which contributes to these goals. Because of the dire necessity to respond to the COVID-19 pandemic, Biophilic Urbanism includes discussion of our need for connections, both to nature and one another, and the physical characteristics of cities and buildings relative to the contagious qualities of the air-borne virus. Case studies, found throughout the world, are presented illustrating detailed biophilic planning and design strategies. The book will be of use to practitioners and students in the fields of natural and social sciences, behavioral science and psychology, environmental engineering, health and wellness professionals, architecture, landscape architecture, interior architecture, and planning"--
OCLC-licensed vendor bibliographic record.
Keywords: Urban ecology (Sociology); City planning -- Environmental aspects; Sustainable development; Nature -- Effect of human beings on; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development